Hydroponic Method as a Solution for Planting Vegetables in Acidic Land - Setiawati Setiawati; Nova Tribuyana; Sergius Dwi Rajasa (Altifani Journal: International Journal of Community Engagement, 2023)
The use of hydroponic method in utilizing yard land for growing vegetables has been used for a long time in Indonesia. Utilizing this method is very helpful during the dry season, very beneficial for the farming community. This method does not require a lot of water and does not take long to produce. The solution for planting vegetables using the hydroponic method in Telang Sari Village, Tanjung Lago District, Banyuasin Regency, South Sumatra Province is the right method for farmers, this is because the water conditions in this area are classified as acidic so the only plants that can be cultivated are rice and corn. The results of the survey in the field showed that the farming community met their vegetable needs by bringing in or buying from the main market in Palembang city, which is quite far from Telang Sari village, so the vegetables they bought were more expensive and less varied. This extension activity aims to introduce the hydroponic method as a solution for providing vegetables on acidic land for the people of Telang Sari village. This community empowerment activity uses counseling methods (lectures and discussions), demonstrations and evaluations. The results of this activity show that the farming community in Telang Sari Village gave a good response, was enthusiastic in carrying out the demonstration and was able to understand each series of stages of activities that will be carried out in cultivating vegetables using hydroponic method.